Description of the acoustical interaction and synchronization between duetters of the Large-footed Finch (Pezopetes capitalis) - Trejos Araya, Carla (2017)
Duets are highly coordinated acoustical displays produced by two individuals. Studying the structure of duet songs and its causes is essential to understand the ecological role and evolution of this form of communication. Our goals in this study were to describe the structure of the duet of the Large-footed Finch, the temporal synchronization of each individual, and to test the effect of provoked (playback) duets. We recorded birds at Cerro de la Muerte, Costa Rica and simulated territory intrusions using playback trials. The duet of this species consisted of overlapping notes between both members of a mated pair, which were emitted either randomly or periodically. Temporal synchronization was similar between both individuals in a mated pair. Both partners adjust the silent intervals between notes in response to the duration of its partner’s note. The high frequency of the second part of the duet of this species decreased with time and the second individual, in duetting this part, not only synchronized its notes temporally with the first individual, but also synchronized the high frequency. The high frequency of the first note the second individual sung was a bit lower than the previous note sung by the first individual. Finally, birds responding to provoked duets produced duets with higher frequency and higher rate of notes compared to unprovoked duets. Our results provide information on the temporal and frequency synchronization in duets of an endemic emberizid and provide new information about a less reported vocal behaviour in bird duets, the acoustic frequency coordination.